On The Big Bang Theory's Success. - CLEMENS, WILL (Pennsylvania Literary Journal (2151-3066))
The article discusses philosophies of causation or causality as described in Upanisheds depicted at the beginning of "The Big Bang Theory" showed in the CBS. It is noted that Ernst Myer's "Cause and Effect In Biology" and Edward Lorenz's "Predictability: Does the Flap of Butterfly's Wing in Brazil Set Off a Tornado in Texas" discuss causality in terms of proximal and distal causes.